HUBUNGAN STRUKTUR MODAL DAN KINERJA KEUANGAN - I Made Yogantara; Liliana Inggrit Wijaya (Journal of Management and Business, 2010)
This study's aim is to test the relationship between capital structure and financial performance of the banking industry in Indonesian Stock Exchange. Institutional ownership, size, risk, market power, and organization structure were employed as control variable to test the affect of capital structure to the financial performance. Market average price of input, market average price of output, size, risk, and market power were employed as control variable to test the affect of financial performance to the capital structure. This study found that capital structure and it's quadrative form, institutional ownership, size, risk, market power, and organization structure simultaneously affect financial performance of the banking industry significantly. This study also found that financial performance and it’s quadrative form, market average price of input, market average price of output, size, risk, and market power simultaneously unaffect capital structure of the banking industry significantly.